Numerical Investigation on Flame Stabilization of Cavity-Based Scramjet Combustor Using Compressible Modified FGM Model - Qi Zhang; Weibing Zhu; Dongchao Yang; Hong Chen (International Journal of Chemical Engineering)
The technology of flame stabilization on cavity-based scramjet combustor has great significance in the field of future spacecraft. In this paper, a compressible modified FGM model was established based on the idea of the flamelet model, which was adopted to simulate the unsteady combustion process of the hydrogen transverse jet in the upper cavity of the scramjet. The results show that the compressible modified FGM model can accurately reflect the flow field and the propagation process of the flame in the supersonic cavity, and can capture the fine shock structure in the flow field. The coupling effect of shock waves and shear layer cause the shear layer to quickly destabilize, resulting in the turbulence effect, which promotes the mixing of air and fuel. The boundary layer separation at the upper wall of the combustion chamber will reduce the stability of the shear layer.